Marital quality and attachment: The mediator role of conflict resolution styles - Patrícia Scheeren; Rebeca Veras de Andrade Vieira; Viviane Ribeiro Goulart; Adriana Wagner (Paidéia (Ribeirão Preto), 2014)
Certain variables can act as mediators between marital quality, social and emotional aspects of the individuals and their context. The aim of this study was to investigate the role of conflict resolution styles as mediators between attachment styles and marital quality. A total of 214 couples participated in the present study aged between 18 and 75 years, residents in Southern Brazil. Three scales were administered: The Conflict Resolution Style Inventory, Golombok Rust Inventory of Marital State and Adult Attachment Scale. Results indicate that the styles of conflict resolution (positive problem solving, conflict engagement, withdrawal and compliance) mediate the relationship between attachment and marital quality. A difference between husbands and wives was observed. These findings suggest the importance of expanding the repertoire of positive strategies of conflict resolution of the couples for the promotion of marital quality.